Koperasi sebagai Landasan Ekonomi - Ayu Maretta Maharani; Ulfatul Khasanah (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
The term cooperative is certainly familiar to us. If referring to Law No. 17 of 2012 article 1, a cooperative is defined as a legal entity established by an individual or a cooperative legal entity, with the separation of the wealth of its members as capital to run a business, which meets common aspirations and needs. In its implementation, cooperatives not only have goals, principles or principles, but also a foundation. As a unique business entity, cooperatives are different from other business entities. In this case, it can be seen from its membership, where cooperative members are known to have dual identities. Dual identity here means that cooperative members are owners and also users of cooperative services. Indonesian cooperatives are the identity of Indonesian business entities that are established on various foundations. The foundation of this cooperative includes ideal, constitutional, mental and operational foundations.